Alcohol intake and cigarette smoking: Impact of two major lifestyle factors on male fertility - Gaur Dushyant; Talekar Manju; Pathak Ved Prakash (Wolters Kluwer Medknow Publications, 2010)
Context: Lifestyle factors, like alcohol intake and cigarette smoking, have been reported to affect male fertility. Aims: To find out the specific impact of alcohol and smoking on semen quality of male partners of couples seeking treatment for primary infertility. Materials and Methods: From the semen samples analyzed in our andrology laboratory, results of 100 alcoholics and 100 cigarette smoker males were studied following WHO guidelines and compared with 100 strict nonalcoholic and nonsmoker males for presence of asthenozoospermia, oligozoospermia and teratozoospermia. Statistical Analysis: Data was analyzed by F- test using Microsoft Office Excel 2003. Results: Only 12% alcoholics and six per cent smokers showed normozoospermia compared to 37 % nonalcoholic nonsmoker males. Teratozoospermia, followed by oligozoospermia dominated alcoholics. Overall impact of asthenozoospermia and teratozoospermia, but not of oligozoospermia, was observed in smokers. Light smokers predominantly showed asthenozoospermia. Heavy alcoholics and smokers showed asthenozoospermia, teratozoospermia as well as oligozoospermia. Conclusions: Asthenozoospermia, the most common semen variable in our study, can be an early indicator of reduction in quality of semen. Alcohol abuse apparently targets sperm morphology and sperm production. Smoke-induced toxins primarily hamper sperm motility and seminal fluid quality. Progressive deterioration in semen quality is related to increasing quantity of alcohol intake and cigarettes smoked.